Effect of sodium monofluorophosphate and phosphates on mechanical properties and water resistance of magnesium oxychloride cement. (May 2022) - Guo, Yingying; Zhang, Y.X.; Soe, Khin
Abstract: Weak water resistance of magnesium oxychloride cement (MOC), an eco-friendly construction material, has been a notorious and critical issue of MOC, restricting its application to mostly indoor with dry service environment. In this paper, sodium monofluorophosphate (MFP) is innovatively used, the first time, as a modifier to enhance the water resistance of MOC, as the PO3 F 2− ions in MFP solution form amorphous phase in MOC, which helps to improve the water repellence of MOC. The effect of MFP with different content, different mixing and curing methods on water resistance of MOC is studied. The effect of phosphates, including phosphoric acid (H3 PO4 ) and soluble phosphates (KH2 PO4 ) with various content on water resistance of MOC is also investigated and compared with the effect of MFP on the water resistance of MOC. The effects of these additives on the physical and mechanical properties of MOC, such as setting time, fluidity, compressive strength, flexural strength, are studied. To reveal the water resistance mechanism, XRD, FTIR, TG/DSC, MIP and SEM-EDS are conducted on the modified MOC. It is found that MFP has similar effect on the mechanical properties of MOC as H3 PO4 and KH2 PO4, and they all significantly increase the flexural strength, slightly decrease the compressive strength, and remarkably increase the water resistance of MOC. The highest compressive strength retention coefficient of 0.84, 0.98, and 0.95 was achieved for 1% KH2 PO4 -MOC, 1% H3 PO4 -MOC, and 1% MFP-MOC respectively. From the microscale study, it is found that the addition of H3 PO4, KH2 PO4, and MFP changes the growth direction and morphology of the phase 5 crystals, which contributes to the increase of the water resistance of MOC.